2013
DOI: 10.6061/clinics/2013(07)16
|View full text |Cite
|
Sign up to set email alerts
|

Improved relationship between left and right ventricular electrical activation after cardiac resynchronization therapy in heart failure patients can be quantified by body surface potential mapping

Abstract: OBJECTIVES:Few studies have evaluated cardiac electrical activation dynamics after cardiac resynchronization therapy. Although this procedure reduces morbidity and mortality in heart failure patients, many approaches attempting to identify the responders have shown that 30% of patients do not attain clinical or functional improvement. This study sought to quantify and characterize the effect of resynchronization therapy on the ventricular electrical activation of patients using body surface potential mapping, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…[ 8 ] Another BSPM approach based on measurement of QRS duration in 87 body surface unipolar leads showed that regional activation time in the RV increased in biventricular pacing, but it was compensated for by an even greater decrease in activation time in the LV, therefore the effect of CRT could be optimised by decreasing the inter-regional RV–LV gradients. [ 23 , 24 ] In addition, BSPM parameters of ventricular repolarisation dispersion such as T peak –T end interval, T peak –T end integral, and T wave amplitude were reduced compared with sinus rhythm under biventricular pacing, whereas RV or LV pacing resulted in increased dispersion of repolarisation. [ 9 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 8 ] Another BSPM approach based on measurement of QRS duration in 87 body surface unipolar leads showed that regional activation time in the RV increased in biventricular pacing, but it was compensated for by an even greater decrease in activation time in the LV, therefore the effect of CRT could be optimised by decreasing the inter-regional RV–LV gradients. [ 23 , 24 ] In addition, BSPM parameters of ventricular repolarisation dispersion such as T peak –T end interval, T peak –T end integral, and T wave amplitude were reduced compared with sinus rhythm under biventricular pacing, whereas RV or LV pacing resulted in increased dispersion of repolarisation. [ 9 ]…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies 16 , 17 , 21 described the BSPM patterns during ventricular depolarization in persons with conduction disturbances in the His-Purkinje system. In patients with a complete right bundle branch block (RBBB), the breakthrough of the excitation on the ventricular subepicardium (which is reflected by the formation of the “saddle” potential distribution on the BSPMs) is noted at 44 ms after the onset of activation of the heart ventricles, in patients with incomplete RBBB – at 38 ms after the onset of ventricular activation.…”
Section: Discussionmentioning
confidence: 99%
“… 11 - 13 Previously, BSPM was applied in order to investigate the ventricular electrical activation in patients with intraventricular conduction abnormalities. 14 - 17 Studies of ventricular depolarization by means of BSPM in first-degree AV block have not been conducted in athletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last three decades, thereby, we developed pioneering studies in all the specialties of Cardiology, including our partnership with colleagues developing doctoral theses at InCor HCFMUSP. [4][5][6][7][8][9][10][11][12][13] The Biomedical Engineering Department of InCor HCFMUSP has been working on the development of a fully nationalized 64-lead BSPM equipment since 2016, with the contribution of the Electrocardiography Unit of InCor.…”
mentioning
confidence: 99%